Occasional Tillage in a Wheat-Sorghum-Fallow Rotation: 2022 Growing Season - John D. Holman; Augustine K. Obour; Lucas A. Haag; Mikaela A. Lawrence (Kansas Agricultural Experiment Station Research Reports, 2023)
Beginning in 2012, research was conducted near Garden City and Tribune, KS, to determine the effect of a single tillage operation every 3 years on grain yields in a wheat-sorghum-fallow (WSF) rotation. Treatments included no-till, single tillage post wheat harvest in mid-August, and single tillage mid-June during the fallow phase. This study was revised with two additional more intensive tillage treatments since 2019. The two additional treatments were 1) two tillage operations during the fallow phase and 2) one tillage during fallow phase and one tillage post wheat harvest. Grain yield varied greatly by year and location. Wheat yields ranged across years from mid-20s to 90 bu/a at Tribune and less than 10 to 100 bu/a at Garden City. Grain sorghum yields ranged from 40 to greater than 140 bu/a, depending upon year and location. Wheat yields tended to be greater with a single or two tillage operations during the fallow phase, and less with single tillage post wheat harvest at Garden City. Grain sorghum yield was less at Tribune when tilled post wheat harvest. This indicates that if a single tillage operation is needed to control troublesome weeds, that tillage during fallow prior to wheat planting may be better than tillage after wheat harvest. This study supports the hypothesis that if herbicide-resistant weed populations are high enough to cause yield reductions, then tillage might improve yields.
Keywords: No-till; herbicide resistant weeds; crop rotation; sorghum; wheat; fallow